The Imagery Models of Mathematics Teacher Candidates on Graph of Rational and Irrational Functions - Darmadi, Darmadi (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2018)
Mathematics teacher candidates are required to have both expertise and communication skills. Therefore, they should have a good imagery model. The present study is a descriptive qualitative researchÂ that involved the students of mathematics education program, FKIP, Universitas PGRI Madiun. The result shows there are 10 models of rational-irrational function graphs that are proposed by the candidates of mathematics teacher involved in the present study.. Mathematics lectures should enrich learning activities and materials to stimulate and develop students' capability in devising the graphs of rational-irrational functions.